Towards the Ideologies on the Developments of Bedhaya Dances in the Contemporary Age - Sawitri, Sawitri; Sudardi, Bani; Abdullah, Wakit; Chaya, Nyoman (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2017)
This present paper provides a descriptive analysis toward a traditional court dance called Bedhaya, one of the cultural products of the Javanese community in Surakarta which evolved into its modern version Bedhayan due to the flow of global culture. By applying the theories of Hermeneutics, Ideology, Aesthetics and Semiotics, the data are inferred according to the purposed questions. The inquiry is directed to infer the factors encompassing Bedhaya dance such as its emergence and the development, relationship with the existence and its role in the society, the relationship with systems within the society or with various interests. The results showed that the Bedhayan dance as developed by the local artists or choreographers in Surakarta as a realization of the local communityâs thought, norm and principle (ideology) which covers both the economic and freedom interests. The ideologies reflected from the attitudes of the supporting community (of dancers and choreographers) toward Bedhayan dance are identified to imply the self-existence, freedom, political, economic, and market interests. The emergence Bedhayan dance was motivated by thoughts of the artists in constructing the dance movements to fit the purpose and function of current art creation. All the changes are deemed to be able to increase the economic welfare of performers, choreographers and the government on the tourism potentiality of the nation. However, there is the dangerous aspects in the development of a cultural dance to view it as a mere commodity, which at the end would give impressions of profanity, commercialization, even the shifts on the traditional values of the dance.